Hormone replacement therapy with L-thyroxine promotes working memory and concentration in thyroidectomized female patients after differentiated thyroid carcinoma. (March 2020) - Cordes, Joachim; Woite, Maya; Engelke, Christina; Regenbrecht, Gunnar; Kahl, Kai G; Schmidt-Kraepelin, Christian; Henning, Uwe; Kamp, Daniel; Klimke, Ansgar
Objective: It is well established that long-term hypothyroidism is associated with cognitive deficits. Based on recent literature, we hypothesized that pharmacologically induced euthyroidism would lead to improved cognitive performance compared to a hypothyroid state. Methods: We analyzed data from 14 nondepressed thyroidectomized female patients after differentiated thyroid carcinoma during hypothyroidism (due to a four-week withdrawal of thyroid hormone, T1) and euthyroidism brought about by substitution with L-thyroxine (T2). At both measurement points, patients completed a cognitive test battery as our dependent measure and Beck's Depression Inventory to control depressive states. Results: A Wilcoxon signed-rank tests revealed a significant improvement in the Rey–Osterrieth complex figure test (cognitive reproduction), Z = −3.183, p = 0.001, and the D2 concentration score, Z = −1.992, p = 0.046 in euthyroidism compared to hypothyroidism. Conclusions: Our results confirm that hormone replacement therapy with L-thyroxine promotes cognitive reproduction and concentration in thyroidectomized female patients after differentiated thyroid carcinoma.